The Association between Electromagnetic Exposure from Mobile Phone or Laptop Computer with Sleep Qualityof Medical Student - Widhiastuti, Silvia Khasnah; Wulandari, R.Aj. Sri; Hanim, Diffah (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Background. Mobile phone and laptop computer were emitting electromagnetic field while being operated. Those electromagnetic field were suspected to affect sleep quality. Poor sleep quality could decrease concentration, cognitive competences, social interaction, and health. Those could manifest on medical studentsâ academic and nonacademic achievement. This research aims to analyse the association between electromagnetic exposure from mobile phone or laptop computer with sleep quality of medical students. Method. This was an analytic observational research with cross sectional design,Â which held in Faculty of Medicine, Sebelas Maret University, on December 2015. The amount of 150 medical students were selected by purposive sampling. Electromagnetic exposure from mobile phone and laptop computer was obtained by Mobile Phone or Laptop Computer Usage Questionnaire. Electromagnetic exposure was measured by mobile phone or laptop computer on top of lap usage duration per day. Sleep quality was obtained by PSQI questionnaire. Data were statistically analyzed using Spearman test with SPSS for Windows edition 20. Result. This research involved 41 males and 109 females. The amount of 139 subjects (92.7%) used mobile phone in high level, whereas 73 subjects used laptop computer above their laps. From those 73 subjects, 52 subjects (71.2%) used laptop computers in low level. The Spearman analysis indicated that there was no significant association between electromagnetic exposure from mobile phone and sleep quality (p=0.198; r=0.106) as well as electromagnetic exposure from laptop computer and sleep quality (p=0.133; r=-0.178) of medical students. Conclusion. There were no significant associations between electromagnetic exposure from mobile phone or laptop computer with sleep quality of medical student. Keywords:electromagnetic exposure, mobile phone, laptop computer, sleep quality